2009
DOI: 10.1167/iovs.08-2328
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Fibroblasts from Patients with Thyroid-Associated Ophthalmopathy Overexpress CD40: CD154 Hyperinduces IL-6, IL-8, and MCP-1

Abstract: Purpose Fibroblast diversity represents an emerging concept critical to our understanding of tissue inflammation, repair and remodeling. Orbital fibroblasts heterogeneously display Thy-1 and exhibit unique phenotypic attributes that may explain the susceptibility of the human orbit to thyroid-associated ophthalmopathy (TAO). In the current study we investigate the role of CD40 ligation upon macrophage chemoattractant protein -1 (MCP-1), IL-6 and IL-8 expression in fibroblasts from patients with TAO. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
144
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 43 publications
6
144
1
Order By: Relevance
“…There are few effective pharmacological treatments for TED due, in part, to a poor understanding the pathogenic mechanisms leading to clinical manifestations of TED. Current evidence, including data from our laboratories (3,47,48), suggests that activation of orbital fibroblasts by infiltrating inflammatory cells, particularly T cells and mast cells, plays an important role in TED pathogenesis (49). Orbital fibroblast proliferation and ECM production, particularly HA (50,51), are key events that contribute to manifestations of TED, such as periorbital edema, exophthalmos, and extraocular motility dysfunction (1,52).…”
Section: Discussionmentioning
confidence: 99%
“…There are few effective pharmacological treatments for TED due, in part, to a poor understanding the pathogenic mechanisms leading to clinical manifestations of TED. Current evidence, including data from our laboratories (3,47,48), suggests that activation of orbital fibroblasts by infiltrating inflammatory cells, particularly T cells and mast cells, plays an important role in TED pathogenesis (49). Orbital fibroblast proliferation and ECM production, particularly HA (50,51), are key events that contribute to manifestations of TED, such as periorbital edema, exophthalmos, and extraocular motility dysfunction (1,52).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of circulating TSHR+ fibrocytes is increased in patients with GD, and TSH induces the production of IL-6, IL-8, monocyte chemoattractant protein 1 (MCP-1), and TNF-a (11). Orbital fibroblasts from patients with GD express high levels of CD40, and in response to CD40L, these cells produce hyaluronan and cytokines, such as IL-6, IL-8, and prostaglandin E2 (PGE2) (54). Moreover, an increased frequency of CD40+ fibrocytes has been observed in the blood and orbital tissues of patients with GD compared with controls, and the CD40-CD40L signaling pathway in these cells can induce production of IL-6, IL-8, MCP-1, and TNF-a (20).…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al (2009) CCL2. Furthermore, Chen et al (2008) found that the expression of CCL2 was higher in GO orbital fat than in the orbital fat of controls and suggested that macrophage infiltration may play an important role in the pathogenesis of GO via overexpression of CCL2.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al (2009) showed that orbital fibroblasts from patients with GO overexpress CD40 and that CD154 (the ligand for CD40) upregulated the expression of CCL2. Furthermore, Chen et al (2008) found that the expression of CCL2 was higher in the orbital fat of GO patients than in controls.…”
Section: Introductionmentioning
confidence: 99%